Morphological effect of dichloromethane on alfalfa (Medicago sativa) cultivated in soil amended with fertilizer manures. Issue 3 (23rd February 2021) - Dardouri, Sana; Jedidi, Asma; Mejri, Sabrine; Hattab, Sabrine; Sghaier, Jalila
Abstract: In this work, we investigated the morphological effect of dichloromethane (DCM) on alfalfa ( Medicago sativa ) plant. We studied in vitro the influence of its concentration on alfalfa germination. The plants were placed in pots for 15 weeks, and exposed to increasing concentrations of DCM (50 µg L −1 and 84 mg L −1 ). In addition, we examined the effect of two manures (cow and sheep), which were applied to a contaminated soil, on alfalfa plant growth. The effect of the presence of dichloromethane is obvious even in plant–soil manure system. In fact, in the event of contamination, the soil–cow manure mixture represents the best setting medium for the Alfalfa plant compared to other environments, regardless of the contamination level. Indeed, the presence of two types of manure does not allow the suppression of the inhibitory effect of dichloromethane on the mass of the dry matter of the aerial part which is 18.38% for the cow manure-amended soil and 13.96% for the sheep manure-amended soil.